Peran Motivasi Kerja Pada Pengaruh Kepemimpinan Terhadap Kinerja Karyawan - Suryadi Suryadi; Sutianingsih Sutianingsih (ITB AAS INDONESIA, 2023)
The purpose of this study was to find out how the concept of work motivation can be used to manage the existing relationship between leadership and employee performance. Quantitative research methodology was applied in this study. Data were obtained through questionnaires and samples of 115 workers. The data analysis methodology used is path analysis and descriptive analysis. Based on the results of the study, all variables have a significant influence, evidenced by: Leadership affects employee performance and motivation. Worker motivation affects performance. This approach uses work motivation as a mediating variable between job placement characteristics and employee performance because the indirect influence is stronger than the direct influence.